Different times effect of fermentation oil palm empty fruit bunches and composition planting media on the growth of amaranth - Fransiska, Sherly; Masitah; Jailani; Nasution, Ruqoyyah; Rosrinda, Eadvin (Genbinesia Journal of Biology, 2022)
Oil palm empty fruit bunches (OPEFB) are underutilized waste. The combination of OPEFB fermentation and eggshell powder as a planting medium, aims to determine the effect of the combination of treatment differences in OPEFB fermentation time and composition of growing media on the growth of amaranth (Amaranthus tricolor). This study consisted of 6 treatment combinations, 4 replications, completely randomized factorial design method, with the parameters of plant height (cm), number of leaves (strands), and total fresh weight (grams). Data were collected at the age of 7, 14 and 21 DAP. Analysis of variance and the smallest significant difference test (BNT) level 5% were used. The results of the analysis showed that the composition of the growing media had a significant effect (Fcount > Ftable), From the results of the study, it was found that the most optimal treatment for the composition of the growing media was W2K3 treatment with a composition of 3 kg of soil, 20 grams of eggshell powder, and 200 grams of OPEFB fermentation for 21 days. The interaction factor of these two factors had a significant effect (Fcount > Ftable) on plant height 21 DAP (4.697 > 3.55).